Senegal : Staff Report for the 2004 Article IV Consultation and Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Nonobservance of Performance Criteria and Rephasing of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2006)
Senegal achieved robust economic growth and low inflation under the economic program. Executive Directors emphasized the need to correct slippages in fiscal governance and transparency to ensure budgetary discipline and strengthen procurement rules and practices. They appreciated the action plan for the development and soundness of the financial system, simplifying loan recovery procedures and improving the efficiency of the judiciary system to reduce nonperforming loans and increase credit availability. They welcomed the comprehensive framework for macroeconomic, structural, and social policies to foster growth and reduce poverty.